BGP Routing Changes: Merging Views from Two ISPs - Teixeira, Renata; Agarwal, Sharad; Rexford, Jennifer (CCR, 2005)
Large ISPs experience millions of BGP routing changes a day. In this paper, we discuss the impact of BGP routing changes on the flow of trafffic, summarizing and reconciling the results from six measurement studies of the Sprint and AT&T backbone networks.